BK channel β1-subunit deficiency exacerbates vascular fibrosis and remodeling but does not promote hypertension in high fat fed obesity in mice - Xu, Hui (J Hypertens, 2015)
OBJECTIVE: Reduced expression or increased degradation of BK (large conductance Ca(2+)-activated K(+)) channel β1-subunits has been associated with increased vascular tone and hypertension in some metabolic diseases. The contribution of BK channel function to control of blood pressure (BP), heart rate (HR) and vascular function/structure was determined in wild-type and BK channel β1-subunit knockout mice fed a high-fat or control diet. METHODS AND RESULTS: After 24 weeks of high-fat diet, wild-type and BK β1-knockout mice were obese, diabetic, but normotensive. High-fat-BK β1-knockout mice had decreased HR while high-fat-wild-type mice had increased HR compared with mice on the control diet. Ganglion blockade caused a greater fall in BP and HR in high-fat mice than in mice on the control diet. β1-adrenergic receptor blockade reduced BP and HR equally in all groups. α1-adrenergic receptor blockade decreased BP in high-fat-BK β1-knockout mice only. Echocardiographic evaluation revealed left ventricular hypertrophy in high-fat-BK β1-knockout mice. Although under anesthesia, mice on a high-fat had higher absolute stroke volume and cardiac output, these measures were similar to control mice when adjusted for body weight. Mesenteric arteries from high-fat-BK β1-knockout mice had higher norepinephrine reactivity, greater wall thickness and collagen accumulation than high-fat-wild-type mesenteric arteries. Compared with control-wild-type mesenteric arteries, high-fat-wild-type mesenteric arteries had blunted contractile responses to a BK channel blocker, although BK α-subunit (protein) and β1-subunit (mRNA) expression were unchanged. CONCLUSIONS: BK channel deficiency promotes increased sympathetic control of blood pressure, and vascular dysfunction, remodeling and fibrosis, but does not cause hypertension in high-fat fed mice.